Prostate cancer in Cali, Colombia, 1962-2011: incidence, mortality and survival - Jaime Alejandro Restrepo; Luis Eduardo Bravo; Herney Andrés García-Perdomo; Luz Stella García; Paola Collazos; Jorge Carbonell (Instituto Nacional de Salud Pública, 2014)
Objective. To analyze the trend in prostate cancer survival, incidence and mortality rates in Cali, Colombia from 1962 to 2011. Materials and methods. Based on the Cancer Registry of Cali, Colombia and the mortality registry of the City's Public Health Secretary, incidence, mortality age-standardized rates and relative survival were calculated during 1962-2011. Results. Prostate cancer incidence rates increased sharply between 1986 and 2002 (APC: 6.21%) and then leveled off. Mortality diminished in 1997 in men older than 70 years-old while in men aged 50-69 years declined since 1981. The 5-year-relative-survival was 69.8% (CI95% 67.5-72.0) and it was significantly associated with age, quinquennial period of diagnosis and socioeconomic strata. Conclusion. The increase in incidence rates of prostate cancer in time coincides with the implementation of the PSA in Cali. There is evidence of improvement in prostate cancer survival, and decreased prostate cancer mortality.